Optimalisasi proses rapid prototyping dan user experience testing dalam pengembangan produk keyboard mechanical modular MEYKE A.01 V2 - Alvian Fajar Setiawan; Chris Chalik; Terbit Setya Pambudi; Jaisy Muzaffar Safruddin (Institut Seni Indonesia Yogyakarta, 2026)
This study discusses the integration of rapid prototyping and user experience testing in the development of the MEYKE A.01 modular mechanical keyboard. Rapid prototyping is applied to produce prototypes quickly and iteratively through 3D modeling and additive manufacturing, enabling early evaluation of the physical design, casing structure, and modular system. User experience testing is then conducted to assess typing comfort, switch responsiveness, keycap stability, and overall ergonomics. This research employs a qualitative approach involving concept development, prototype fabrication, user testing, and evaluation analysis. The results indicate that integrating these methods enhances the alignment of the design with user needs and accelerates the identification and refinement of design issues. Thus, this approach is effective in producing a modular keyboard that is functional, ergonomic, and user-experience oriented.